Natural Hybridization of Lepisosteids: Implications for Managing the Alligator Gar. (10th March 2017) - Bohn, Sandra; Kreiser, Brian R.; Daugherty, Daniel J.; Bodine, Kristopher A.
Abstract: The Alligator Gar Atractosteus spatula has become a focal species of management and conservation due to declining populations and growing popularity among anglers. The Alligator Gar is sympatric with the Longnose Gar Lepisosteus osseus and Spotted Gar L. oculatus throughout much of its range, providing the potential for hybridization that can complicate conservation efforts. Hybridization between gars has been documented in captivity; however, natural (i.e., wild) hybridization has not been formally assessed. Population sampling and genetic analyses of Alligator Gars in Texas provided an opportunity to examine hybridization among gars and to assess the potential implications for Alligator Gar management. Specifically, we (1) developed markers to distinguish lepisosteid species and their hybrids, (2) characterized hybridization between species, and (3) assessed our ability to differentiate hybrids from parent species via field evaluation of snout morphology. Fin tissue samples from Alligator Gars and putative hybrids, along with a reference sample of Longnose Gars and Spotted Gars, were genotyped for a mitochondrial locus, two nuclear introns, two nuclear exons, and nine microsatellite loci. Natural hybridization was confirmed: 17 F1 Alligator Gar (female) × Longnose Gar (male) crosses and one F1 Longnose Gar × Spotted Gar were identified, as well as three additional hybrids of uncertain ancestry. Field identification of putative hybrids based on snout morphology was conservative: 21 of 26 (81%) were correctly classified as hybrid individuals, with no false negatives. Our data confirm that sympatric lepisosteid populations do hybridize and that general monitoring of hybridization rates can be accomplished afield. We recommend monitoring of hybridization between sympatric gar populations due to the risks associated with genetic introgression, particularly in systems with depressed Alligator Gar stocks. Received September 5, 2016; accepted November 21, 2016 Published online March 10, 2017